Understanding the problems and prospects of the Muslim unity an analysis of Mawdudi's views - Amanullah, Muhammad; Islam , Tajul (International Islamic University Malaysia, 2011)

(untitled)
Mawdudi's thesis of Muslim unity touches core of the issue as he emphasizes on finding the basics of understanding the Muslim unity. Any attempt to set the theory of Muslim unity may not get the practical dimension until the standards of its understanding are laid out. In other words, it can be said that setting the basics of understanding the unity is a prerequisite for shaping effective theory of Muslim unity. After a thorough exploration, MawdËdÊ's works on Muslim unity appear to be written very systematic and methodological manner. He critically scrutinizes the basics of understanding the unity. As he claims, one must find out the common grounds that especially bind Muslim countries together and all Muslims in general; and the issue of Muslim unity may remain vague until the Islamic culture is completely conceived of. He says that "the unity of Islamic world cannot be conceived of without Islamic culture". Mawdudi recommends that the common things which unite all Muslims together are the common beliefs and thought, common culture, common moral system, civilizational relationship, vitality of the concept of one Ummah, universal brotherhood and geographical location of the Muslim world. This paper is devoted to critically analyze Mawdudi’s ideas on Muslim unity.